2016
DOI: 10.1016/j.ophtha.2016.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Recurrent Retinopathy of Prematurity after Intravitreal Bevacizumab Monotherapy

Abstract: PURPOSE To determine (1) incidence, (2) risk factors, (3) risk period, and (4) characteristics of recurrent retinopathy of prematurity (ROP) treated by intravitreal bevacizumab (IVB) monotherapy. DESIGN Retrospective case series. PARTICIPANTS Premature infants developing Type 1 ROP [subdivided into ROP stage 3+ and aggressive posterior ROP (APROP)] in zone I or zone II posterior, receiving IVB monotherapy, and followed for at least 65 weeks adjusted age (AA). METHODS Retrospective review of infants who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
122
6
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(157 citation statements)
references
References 40 publications
5
122
6
24
Order By: Relevance
“…In our series, we found that the need for retreatment arose at a mean of 44 weeks’ PMA (range 40–50), some 9.8 weeks post-IVB (range 6–15 weeks). Our recurrence window was somewhat earlier than that reported by Mintz-Hittner et al (mean 51.2 weeks’ PMA (range 46–65), at a mean of 16.2 weeks post-IVB) 9. It seems reasonable to draw the conclusion that use of ‘ultra-low’-dose IVB may be characterised by a slightly different timeline from the higher ‘standard’ dose, namely that the drug takes effect slightly slower and that any recurrence is likely to present more swiftly.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…In our series, we found that the need for retreatment arose at a mean of 44 weeks’ PMA (range 40–50), some 9.8 weeks post-IVB (range 6–15 weeks). Our recurrence window was somewhat earlier than that reported by Mintz-Hittner et al (mean 51.2 weeks’ PMA (range 46–65), at a mean of 16.2 weeks post-IVB) 9. It seems reasonable to draw the conclusion that use of ‘ultra-low’-dose IVB may be characterised by a slightly different timeline from the higher ‘standard’ dose, namely that the drug takes effect slightly slower and that any recurrence is likely to present more swiftly.…”
Section: Discussioncontrasting
confidence: 46%
“…Whereas recurrence of neovascularisation and ‘plus’ disease would seem to be uniformly compelling indications for retreatment, we opted to administer additional treatment in other scenarios judiciously (eg, loculated vitreous haemorrhage obscuring the site of previously resolving neovascularisation). Second, even if we assume our ‘retreatment rate’ to be a valid proxy for the ‘recurrence rate’, it is clear that the demographics of our patient group placed them at especially high risk of recurrence, with our cohort generally having a lower GA and BW than the Mintz-Hittner et al series 9. In our series, we found that the need for retreatment arose at a mean of 44 weeks’ PMA (range 40–50), some 9.8 weeks post-IVB (range 6–15 weeks).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recurrences at the previous ridge or leading edge were found in former APROP but only in the advancing edge in eyes without confluent neovascularization. Retreatment led to slow regression(30). Although most recurrences were seen within 1 year of adjusted age, a report described late reactivation of ROP after bilateral IVB with a tractional retinal detachment in one eye and milder reactivation in the fellow eye at 2.5 years of age(31).…”
Section: Introductionmentioning
confidence: 99%